Os assírios no norte da Síria: questões territoriais em meio ao Estado Sírio e à diáspora - Holtz, Mateus Felipe (2022)
The present work has the general objective of understanding the territoriality of the Assyrians, an ethnic-religious minority in northern Syria - region of the province of al-Hasakah and the Khabour River Valley, amidst the tensions caused by the overlap and territorial dispute between the Government Syria and the Northern Democratic Federation – government institution with a Kurdish majority. To achieve this goal, we proposed a scalar analysis of the social and political action of this Christian minority: a global level, discussing the mobilization of Assyrians in diaspora; a national/regional level, dealing with the insertion of the Assyrians in Syria and its relations with Damascus; a local level, manifested in the defense mechanisms of the territory by the Assyrians regarding the establishment of the Kurds in northern Syria. These three scales are mediated from the Syrian Civil War, when we relate the events involving the Assyrians at different levels of action to David's concepts of imperialism. Harvey, and of empire and multitude, treated by Antonio Negri and Michael Hardt. The result of this research points to the existence of a diffuse Assyrian territoriality, while socially they are divided between rural and peasant communities and urban, peripheral and commercial circles. At the same time, politically, there is a diversity of political positions within Syria, with groups that recognize the Syrian State, sectors that support the Kurdish project and others that remain neutral in the dispute.